Metabarcoding of eDNA for tracking the floral and geographical origins of bee honey. (February 2023) - Pathiraja, Duleepa; Cho, Junghwan; Kim, Junsung; Choi, In-Geol
Graphical abstract: Highlights: Metabarcoding of eDNA for authentication of bee honey. Composition of bacterial DNA in honey differs based on the geographical origin. Plant DNA barcoding can determine monofloral/polyfloral origin of honey. Amplicon sequence variants of honey bee are specific to geographical area. eDNA based approach can complement the traditional honey authentication methods. Abstract: Authentic honey products have a high commercial value and are often falsified via adulteration. Metabarcoding of environmental DNA (eDNA) from bacterial, floral, and entomological sources has recently been proposed as a useful tool for identifying and authenticating floral and geographical origins of bee honey. In this study, eDNA metabarcoding was applied to reveal the bacterial, plant, and honey bee DNA signatures of 48 commercial honey products from six different geographical origins. Bacterial DNA composition in commercial honey showed different relative abundance of Paenibacillus and Bacillus in geographically different samples, and high abundance of Methylobacterium in chestnut honey implying potential use of bacterial DNA composition for honey authentication. Using the chloroplast trnL (UAA) as a DNA marker, floral origins of commercial honey were investigated. Based on floral DNA signatures, 12 monofloral honey samples were identified among the 45 samples tested. Targeted amplicon sequencing of cytochrome oxidase I (COI) gene from entomological DNA identified three different Apis mellifera sequence variants, specific to geographic origin of honey, suggesting that COI can be implemented as a DNA marker to trace the origin of honey. Therefore, the current study demonstrated the potential of eDNA based metabarcoding as a robust tool for evaluating commercial bee honey by exploring their floral and geographical origins.